Ecuadorian Sociology or the Institutionalization of a Strange Discipline. - Altmann, Philipp (2023)
Sociology in Ecuador has existed as an academic discipline since 1915 and since the 1960s as a degree program. Those over 100 years are marked by several harsh ruptures and less visible changes in general tendencies. One main factor related to both ruptures and tendencies are the institutions and institutionalizations of and around sociology. They include universities, professional or cultural associations, journals, the state—but also national and international events and activities of sociologists beyond academia. They produced the conditions of early positivist sociology with its different perspectives, their influence permitted a certain professionalization and internationalization in the 1950s and 1960s—and the almost complete break with earlier sociologies in the 1970s that produced a new style of institutionalization that remains relevant up to the present day. This text will revise the relationship between sociological research and published reflections and the different institutionalizations in which they happened. The main focus is the facilitation or hindrance of a coherent sociological thought in relation to international tendencies and to the academic debate in Ecuador itself. The main texts of the most important sociologists will be analyzed in relation to the institutionalizations that made their production possible or favored a certain style of sociology.